A Transformational-Generative Analysis of Spoken Syntax in TikTok Podcasts: A Study on the Deddy Corbuzier Channel Segment “KTP Wonogiri... Ngomongnya British Abis!!” - Robi'ah Laila; Hapni Nurliana H. D Hasibuan; Dahnilsyah Dahnilsyah; Nur Azizi; Sayyidah Khansa (Universitas Galuh, 2026)
This research discusses the syntactic analysis of spoken sentences in the Deddy Corbuzier Channel podcast on TikTok. The purpose of this study is to describe how sentence structures in spoken language differ from written language and to identify how they reflect Chomsky’s theory of Transformational-Generative Grammar (TGG). This study uses qualitative methods. The research data were taken from selected podcast transcripts from TikTok. To answer the research questions, the researcher applied Chomsky’s theory (1957, 1965) focusing on the relationship between deep structure and surface structure in sentence formation. The results reveal that although the deep structures of the utterances are grammatically correct, the surface structures often show spoken features such as topic fronting, lexical substitution, repetition, fillers, and clause fragmentation. These forms occur naturally in spontaneous conversation and are not considered grammatical errors. Furthermore, the analysis shows that spoken sentences tend to prioritize clarity, emphasis, and emotional expression rather than formal grammatical